Chemical composition and stress dependence of the elastic properties of κ-(Fe, Mn)3AlC thin films. (August 2018) - Herrig, Friederike; Music, Denis; Rueß, Holger; Ravensburg, Anna L.; Pöllmann, Peter J.; Schneider, Jochen M.
Abstract: Although the formation of nanosized κ-precipitates in austenitic Fe-Mn-Al-C matrices cause coherency strains and affect both strength and ductility, the composition and stress dependence of the elastic properties has not been studied systematically for (Fe, Mn)3 AlC ( Pm 3 ¯ m ). An elastic modulus decrease of 49 and 64 GPa upon C- and Al-vacancy formation, respectively, was predicted and experimentally verified and is caused by concomitant weakening in average bond energy. The predicted increase of up to 33 GPa in elastic modulus due to the presence of 2 GPa compressive stress was corroborated experimentally and can be understood by pressure induced bond strengthening. Graphical abstract: Unlabelled Image